A Semantic Reading of Abu l-Majsi l-Andalusi’s Qasida The Bilndness - Masfer Al-Malki, Saeed (Anaquel de Estudios Árabes, 2011)
This paper is concerned with the semantic connotations of lexis in “Blindness” a poem written by Abu l-Makhshi al-Andalusi who died in the period ranging from (796 A.D and 180 A.H ) to( 822 A.D – 206 A.H). The paper is divided into an introduction about the semantic connotations of lexis and the most outstanding trends in this field and the body which is divided into three sections: the first section gives background information about the poet, the second section sheds light on the different aspects of al-Makhshi’s poetical career and the third section is devoted to reading the semantic connotations of the lexis in the poem in question. This last section is divided into three parts: the semantic connotations of the verb, the semantic connotations of the noun and the semantic connotations of the particles. The paper ends with a synopsis.
Keywords: Literature and Poetry of al-Andalus; Abu Al-Majsi Al-Andalusi; Poem of the Blindness.